Implementation challenges of universal basic education policy in Delta State, Nigeria: stakeholders’ roles - Ataphia, Akporehe Dorah; Okiemute, Anho Roseline; Obro, Sunday (Intelektual Pustaka Media Utama, 2026)
The study dwelt on the analysis of implementation challenges of universal basic education (UBE) in public primary schools. The expose facto research design and survey method were adopted to carry out the study. The multistage sampling technique was adopted to select 414 teachers. A self-constructed instrument was used to conduct the study. The instrument’s reliability was tested using Cronbach alpha statistics, which gave a 0.75 alpha coefficient and was deemed reliable. The researcher and six research assistants administered the instrument. Descriptive statistics was used to analyze the research questions, while the hypothesis was tested with t-test statistics. The findings revealed many challenges facing the implementation of UBE in Delta state, which emanate primarily from parents and the government. It was recommended that the government provide adequate funds to provide a conducive environment for learning in school; the government should ensure that parents send their children to school by giving UBE more publicity, enlightening parents on the benefits of educating their wards, and enforcing sanctions to erring parents, among others.